Transcriptional Upregulation of DNA Damage Response Genes in Bank Voles (Myodes glareolus) Inhabiting the Chernobyl Exclusion Zone - Jernfors, Toni; Kesäniemi, Jenni; Lavrinienko, Anton; Mappes, Tapio; Milinevsky, Gennadi; Møller, Anders P.; Mousseau, Timothy A.; Tukalenko, Eugene; Watts, Phillip C. (Frontiers in Environmental Science, 2018)
Exposure to ionizing radiation (IR) from radionuclides released into the environment can damage DNA. An expected response to exposure to environmental radionuclides, therefore, is initiation of DNA damage response (DDR) pathways. Increased DNA damage is a characteristic of many organisms exposed to radionuclides but expression of DDR genes of wildlife inhabiting an area contaminated by radionuclides is poorly understood. We quantified expression of five central DDR genes Atm, Mre11, p53, Brca1 and p21 in the livers of the bank vole Myodes glareolus that inhabited areas within the Chernobyl Exclusion Zone (CEZ) that differed in levels of background radioactivity, and also from control areas outside the CEZ (i.e. sites with no detectable environmental radionuclides) in Ukraine. Expression of these DDR genes did not significantly differ between male and female bank voles, nor among sites within the CEZ. We found a near two-fold upregulation in the DDR initiators Mre11 and Atm in animals collected from the CEZ compared with samples from control sites. As Atm is an important regulator of oxidative stress, our data suggest that antioxidant activity may be a key component of the defense against exposure to environmental radioactivity.